1996
DOI: 10.1001/archinte.1996.00440100065008
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Therapy in Glucocorticoid-Treated Men

Abstract: Testosterone treatment reverses the deleterious effects glucocorticoid drugs on skeletal and soft tissues in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(74 citation statements)
references
References 27 publications
0
72
0
2
Order By: Relevance
“…34 Glucocorticoids also reduce osteoclast apoptosis, 35 thus increasing bone resorption and increase osteocyte apoptosis, an effect that is implicated in the development of avascular necrosis. 35 Indirect effects of glucocorticoids also con- tribute to bone loss; these include hypogonadism, 36 reduced intestinal calcium absorption 37 and increased renal calcium excretion. 38 Glucocorticoid-induced bone loss is particularly rapid in the first few months of therapy and affects both cortical and cancellous bone.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…34 Glucocorticoids also reduce osteoclast apoptosis, 35 thus increasing bone resorption and increase osteocyte apoptosis, an effect that is implicated in the development of avascular necrosis. 35 Indirect effects of glucocorticoids also con- tribute to bone loss; these include hypogonadism, 36 reduced intestinal calcium absorption 37 and increased renal calcium excretion. 38 Glucocorticoid-induced bone loss is particularly rapid in the first few months of therapy and affects both cortical and cancellous bone.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…In asthmatic men receiving long-term GC treatment, testosterone treatment was shown to increase lumbar spine BMD by 5.0% over 12 months [108]. In women treated with GCs for rheumatic disease, nandrolone decanoate significantly increased forearm bone density by 5.1% over 18 months versus baseline (P<0.01) [3].…”
Section: Fluoridementioning
confidence: 92%
“…Serum testosterone concentrations correlate positively with muscle mass and negatively with fat mass [57]. Testosterone replacement therapy increases lean body mass in men with hypogonadism due to aging, HIV infection, and other chronic diseases [58][59][60]. Some but not all studies have reported that testosterone replacement therapy decreases fat mass in hypogonadal men [58,61,62].…”
Section: Treatment-related Changes In Body Compositionmentioning
confidence: 99%